A Brief Report: Community Supportiveness May Facilitate Participation of Children With Autism Spectrum Disorder in Their Community and Reduce Feelings of Isolation in Their Caregivers - Devenish, Bethany D.; Sivaratnam, Carmel; Lindor, Ebony; Papadopoulos, Nicole; Wilson, Rujuta; McGillivray, Jane; Rinehart, Nicole J. (Frontiers in Psychology, 2020)
Children with autism spectrum disorder (ASD) participate at lower rates in their community (Simpson, Adams, Bruck & Keen, 2019), and their caregivers experience higher levels of stress, in comparison to families of typically developing (TD) children (Keenan et al., 2016). The social model of disability positions the environment as the central issue when children with disabilities are unable to participate (Shakespeare & Watson, 2002), yet little is known about the relationship between poor community support, reduced community participation in children with ASD, and caregiver stress. This study examined caregiver perceptions of community supportiveness for the community participation of 48 children with ASD (aged 5-12 years), alongside caregiver-reported child ASD symptom severity, adaptive functioning and caregiver stress. Community supportiveness predicted child involvement, but not attendance, when child characteristics were held constant. Caregiver perceptions of low community supportiveness significantly predicted caregiver feelings of isolation. The importance of modifying community programs to better support inclusion of children with ASD is discussed.